2011
DOI: 10.1242/jcs.079046
|View full text |Cite
|
Sign up to set email alerts
|

Differential roles of kinesin and dynein in translocation of neurofilaments into axonal neurites

Abstract: SummaryNeurofilament (NF) subunits translocate within axons as short NFs, non-filamentous punctate structures ('puncta') and diffuse material that might comprise individual subunits and/or oligomers. Transport of NFs into and along axons is mediated by the microtubule (MT) motor proteins kinesin and dynein. Despite being characterized as a retrograde motor, dynein nevertheless participates in anterograde NF transport through associating with long MTs or the actin cortex through its cargo domain; relatively sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…However, ablation of the NF-H C-terminal tail in mice did not alter axonal transport speed 54 , although this might be explained by a compensatory increase in NF-M phosphorylation 51 . Nevertheless, the current model suggests that NF phosphorylation slows the speed of axonal transport 10,51,55 , possibly by promoting NF bundling, which, in turn, competes with kinesin-mediated NF-MT association 5557 . Determining which kinases phosphorylate which sites in vivo may provide further insight into the significance of NF tail phosphorylation.…”
Section: If Phosphorylation: Multifunctional Ptmmentioning
confidence: 71%
“…However, ablation of the NF-H C-terminal tail in mice did not alter axonal transport speed 54 , although this might be explained by a compensatory increase in NF-M phosphorylation 51 . Nevertheless, the current model suggests that NF phosphorylation slows the speed of axonal transport 10,51,55 , possibly by promoting NF bundling, which, in turn, competes with kinesin-mediated NF-MT association 5557 . Determining which kinases phosphorylate which sites in vivo may provide further insight into the significance of NF tail phosphorylation.…”
Section: If Phosphorylation: Multifunctional Ptmmentioning
confidence: 71%
“…These changes can often affect very specific parts of transport such as different compartments of the axon or the direction of cargo movement away from the cell body or toward the cell body (Shea and Beaty, 2007). Due to the complexity of the nervous system, most of the evidence reporting differential transport effects in pathology are ex vivo (see for example, Brady et al, 1990; Morfini et al, 2007; Motil et al, 2007; Lee et al, 2011; LaPointe et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Imaging of GFP‐tagged NF has demonstrated that NF are transported in axons, moving through NF‐free gaps , or into photo‐bleached segments , though NF also are transported in other forms (NF precursors) . As in the case of vimentin squiggles and particles, transport of NF is dependent on microtubules and requires the microtubule‐motors kinesin (in particular, Kif5A) and dynein . NF also associate with actin and myosin .…”
Section: If Interaction Functionmentioning
confidence: 99%